Association between female cardiometabolic index and infertility: a population-based study - Liu, Junqian; Zhu, Fengya; Wang, Yuan; Wu, Jie (Frontiers in Public Health, 2025)
BackgroundVisceral fat accumulation and dyslipidaemia are associated with infertility symptoms. The cardiometabolic index (CMI) is a comprehensive quantitative measure of central obesity and dyslipidaemia. However, the link between the female CMI and the couple infertility needs to be explored further. Hence, this study aimed to dissect this connection.MethodsThe study used a cross-sectional approach to select 1,641 female participants from the National Health and Nutrition Examination Survey (NHANES), which was conducted between 2013 and 2020. The natural log–transformed CMI (In-CMI) was used to consider the non-normal distribution of CMI. Logistic regression models adjusted for covariates were employed to investigate the association between the In-CMI and couple infertility.ResultsAfter adjusting for all covariates, each 1 unit increase in the In-CMI was associated with a 34% increase in the incidence of infertility (odds ratio [OR] 1.34, 95% confidence interval [CI] 1.10–1.64, p = 0.004). In addition, the association remained statistically significant after dividing the In-CMI into tertiles (T1, T2, and T3). The T3 group, with the highest In-CMI, showed higher odds of infertility compared with the T1 group (OR 2.11, 95% CI 1.38–3.23, p < 0.001). Subgroup and interaction analyses revealed that the association between the In-CMI and infertility depended on a history of treatment for pelvic infection (P for interaction <0.05). The inflection point for a positive linear association between In-CMI and infertility was−0.73.ConclusionThe female CMI is linked to the incidence of couple infertility. Moreover, the female CMI shows significant medical significance for assessing couple infertility risk of childbearing age.